Surface Smoothing by Gas Cluster Ion Beam Using Decreasing Three-Step Energy Treatment - Pelenovich, Vasiliy (2023)
Funding Information: This work was supported by the Hubei Provincial and Municipal Double First-class Talent Construction Start-up Fund in 2022 (Project No. 600460045), the Key R&D program of Hubei Province (Grant No. 2022BAA049), the Science and Technology Planning Project of Shenzhen Municipality (Grant Nos. 2019N032, JCYJ20220530140605011), and the National Key Research and Development Program of China (Grant No. 2022YFB4601000). Publisher Copyright: © 2023 by the authors.